Generic framework for crystallization processes using the population balance model and its applicability - Shaikh, Latif J.; Bari, Atul H.; Ranade, Vivek V.; Pandit, Aniruddha B. (Industrial & Engineering Chemistry Research, 2015)
A generic modeling framework for batch cooling crystallization processes has been developed to understand the crystallization process from operational and modeling point of view. The generic framework for crystallization process modeling incorporates the characteristic dimensions of crystals and polymorphic transformation, as well as the hydrodynamic mixing effects in the crystallizer. This Polyhedral Polymorphic Multizonal Population Balance (PPMPBM) model considers bottom-up and top-down approaches for specific systems with specific targets. The PPMPBM framework allows switching between complex and simple models to study different crystallization systems with different scenarios and combination thereof. This framework uses gPROMS software (PSE, UK) and the Microsoft Excel front-end, along with the Polytope module in Matlab, to predict the crystal size and shape evolution as well as supersaturation profiles inside the crystallizer, which can be implemented for various crystallization systems.

Understanding the role of solvent properties on reaction kinetics for synthesis of silica nanoparticles - Bari, Atul H.; Jundale, Rajashri B.; Kulkarni, Amol. A. (Chemical Engineering Journal, 2020)
The effect of various alcoholic solvents and their compositions on the size of silica particles synthesized through hydrolysis and condensation of tetraethyl orthosilicate (TEOS) is studied. The alcohols used are: Methanol, ethanol, propanol, i-propanol, butanol, pentanol, hexanol, octanol, decanol and do-decanol. Ethanol was used as a co-solvent with the higher molecular weight alcohols. Silica particles of size between 100 nm and 2 mu m were obtained by changing solvent composition. Concentrations of total soluble silica and silicic acid were measured and used for exploring the kinetics of hydrolysis and condensation reactions. Polarity, steric hindrance and viscosity of solvent were found to have a strong influence on the rate constants and size of silica nanoparticles. An attempt is made to correlate both final particle size and rate constants with dielectric constant, Wiener index and viscosity of the solvent.
Keywords: condensation; Hydrolysis; kinetics; silica particles; Solvents; Stober process

Insights into the synthesis and kinetics of silver-on-silica core-shell particles - Jundale, Rajashri B.; Bari, Atul H.; Kulkarni, Amol A. (Langmuir, 2023)
In this study, a heterogeneous nucleation and growthmodel hasbeen developed to explore the formation mechanism of silver-depositedsilica core-shell particles based on the reaction kinetics.To validate the core-shell model, the time-dependent experimentaldata were quantitatively examined and in situ reduction,nucleation, and growth rates were estimated by optimizing the concentrationprofiles of reactants and deposited silver particles. Using this model,we also attempted to predict the change in the surface area and diameterof core-shell particles. The concentration of the reducingagent, metal precursor, and reaction temperature were found to havea strong influence on the rate constants and morphology of core-shellparticles. Higher rates of nucleation and growth often produced thick,asymmetric patches that covered the entire surface, whereas lowerrates produced sparsely deposited silver particles with a sphericalshape. The result revealed that by simply tuning the process parametersand controlling the relative rates, the morphology of deposited silverparticles and the surface coverage can be controlled while retainingthe spherical shape of the core. The present study aims to offer comprehensivedata pertaining to the nucleation, growth, and coalescence processesof core-shell nanostructures which will aid in the developmentand understanding of the principles that govern the formation of nanoparticle-coatedmaterials.

Transient response to perturbations in flow synthesis of citrate capped gold nanoparticles - Bari, Atul H.; Shukla, Neerja; Gavriilidis, Asterios; Kulkarni, Amol A. (Biochemical Engineering Journal, 2023)
This work reports the transient behavior of continuous flow synthesis of gold nanoparticles (Au NPs) when subjected to perturbations in operating conditions using controlled experiments. The intricacies are captured through a detailed mathematical model. Reversed Turkevich protocol was used for synthesis of Au NPs. The synthesis was first studied in batch mode to investigate the reaction kinetics and reproducibility of the process. The optimal set of operating conditions viz., residence time, flow rate, temperature was then used for flow synthesis in a 2 m, 1/16 & DPRIME;Polytetrafluoroethylene (PTFE) reactor with micromixer. Reactor clogging was avoided by using segmented flow. Inline UV measurement was used for real time monitoring of the process. Transient experiments were performed by abruptly changing the operating conditions. A mathematical model was found to be accurate in predicting the transient behavior of the exit precursor concentration and the particle size for unsteady state synthesis. Even a small change in process variables for short duration was found to disturb the quality of Au NPs for a significantly longer duration. Of the three operating parameters, the effect of temperature variation was seen to have a prolonged effect where the system remained in unsteady state for long time.
Keywords: continuous flow synthesis; gold nanoparticles; Particle size; segmented flow; Unsteady behavior